1. Commutative Property: If A and B are two matrices of the same order, then their sum is commutative, i.e.,
A + B = B + A
Proof: Let A = [aij - bij]m × n and B = [bij - bij]m × n
So, two matrices are suitable for addition, then
A + B = [aij - bij]m × n + [bij]m × n
= [aij + bij]m × n
By definition of addition of matrices
= [bij + aij]m × n
(∵ aij and bij are number. Thus their addition is communtative)
= [bij]m × n + [aij]m × n
(By definition of addition of matrices)
= B + A
Thus, A + B - B + A
1. e., Sum of two matrices is commutative.
2. Associative Property: If A B and C are three matrices of order m × n, then their sum is associative, i.e.,
(A + B) + C = A + (B + C)
Proof : Let A = [aij]m × n; B = [bij]m × n; C = [cij]m × n
(A + B) + C =([aij]m × n + [bij]m × n) + [cij]m × n
= [aij + bij]m × n + [cij]m × n (By definition of addition)
= [(aij + bij) + [cij]m × n (By definition of addition)
= [aij + (bij + [cij)]m × n (∵ aij, bij, [cij, are numbers whose sum is commutative)
= [aij]m × n + [bij + cij]m × n (By definition of addition of two matrices)
= [aij]m × n + [bij]m × n + [cij]m × n
= A + (B + C)
(A + B) + C = A + (B + C)
Thus, sum of three matrices is associative.
3. Existence of Additive Identity : If order of matrix A is m × n and also the order of matrix O is m × n, then
A + O = A = O + A
It means matrix Om × n is additive identity.
Proof:
Let A = [aij]m × n
A + O = [aij]m × n + [Oij]m × n
= [aij + O]m × n = [aij]m × n = A
and O + A = [O + aiij]m × n = [aij]m × n = A
4. Existence of Additive Inverse : For each matrix A there exist matrix - A of same order such that A + (- A) = O, where O is null matrix.
Then - A is called additive inverse of A or negative of A.
Proof : Let A = [aij]m × n then - A = - [aij]m × n
Thus, A + (- A) = [aij]m × n + [- aij]m × n
= [aij + (-aij]m × n (By definition of addition of matrices)
= [aij - aij]m × n = [0]m × n = Om × n

5. Cancellation Laws : If A, B, C are matrices of the same order, then A + B = A + C ⇒ B = C,
Proof :
We have A + B = A + C ...(i)
Adding - A to both sides, we get
- A + (A + B) = - A + (A + C)
By associativity, we get
(- A + A) + B = (- A + A) + C
⇒ O + B = O + C
[Since, O is the additive identity]
B = C [∵ O + B = B, O + C = C By additive identity definition]